O poder de investigação criminal do Ministério Público - Teixeira, Rafael Luis Ramos (2016)
The prosecutor's office has its origins in France‟s King Philip IV. In Brazil, was present in most of the Constitutions. Before the current constitution was an organ of executive power. In the current Constitution has acquired autonomy and other guarantees that made this institution has an important role in society, responsible for initiating criminal action and guarantee the defense of democracy, law and society. Its power research had a strong opposition missing in the current Constitution express provision in this regard. Using the theory of implied powers, the Supreme Court ruled that the prosecution can conduct investigative actions provided that it meets certain parameters.